İksa Sistemlerinde Köşe Etkisinin İki Boyutlu Sonlu Eleman Analiz Yöntemi İle İncelenmesi - Cansız, Berna Merve (Fen Bilimleri Enstitüsü, 2014)
Bu tezde iki boyutlu sonlu elemanlar yöntemi kullanılarak, birden fazla kademeli ankrajlarla desteklenen fore kazıklı derin kazı iksa sistemi analiz edilmiştir.Köşe  etkisinin anlaşılabilmesi için köşenin iksa sistemine dik doğrultuda yatay elemanlar olarak tanımlandığı bir diğer model üzerinde deformasyon, efektif yatay gerilme, moment ve kesme kuvveti değerleri incelenmiştir. Bu kapsamda örnek çalışma olarak Çiftçi Towers Zincirlikuyu Projesi kapsamında inşa edilmekte olan rezidans binalarının kazısında uygulanan fore kazık ve öngermeli ankrajlardan oluşan iksa sistemi dikkate alınmıştır.Kazı süresince duvar deplasmanları sürekli ölçülmüş ve duvar davranışı sürekli olarak izlenmiştir. Zincirlikuyu projesi derin kazısı iki boyutlu sonlu eleman modellenmesi yöntemi ile çözülmüştür. Analizi yapılan iksa kesiti için klasik çözümün yanındabir de köşenin etkisinin strut elemanlarla tanımlandığıbir model oluşturulmuştur. Bu analizlerin sonuçları, köşe noktasından 51 m ve 2.5 m mesafelerdeki iki adet inklinometreye ait okumalar ile karşılaştırılmış ve köşe etkilerinin duvar deplasmanlarına yansıması incelenmiştir. Analizlerde yaklaşık 40 m derinliğinde kazı çukuru modellenmiş olup, zemin birimleri sondaj loglarında belirtildiği üzere yüzeyden itibaren 3 m derinliğe kadar dolgu ve devamında ise altere diyabaz olarak tanımlanmıştır. Zemin birimlerine ait mühendislik parametreleri laboratuvar deneylerinden elde edilen verilere göre girilmiş olup, zemin modeli olarak elasto-plastik malzeme modeli olan Hardening Soil modeli kullanılmıştır.Söz konusu proje sahasında yer altı suyuna rastlanmadığından drenajlı malzeme tipi seçilmiştir. Kazı destek sistemi iki palyeli olarak analiz edilmiştir. İlk palyede 1.2 m arayla, 24 m uzunluğunda 100 cm çapında fore kazık, ikinci palyede ise 0.6 m arayla, 20.1 m uzunluğunda 30 cm çapında mini kazıklar modellenmiştir. Analizlerde, uzunlukları 24.5 m ile 39.5 m arasında değişen 4x0.6” ankraj halatları 1.2 m arayla yatay destek elemanı olarak atanmış olup, halatlara 500 kN’luk öngerme yükü uygulanmıştır.Kazı modeli 38 fazda çözülmüş ve analizler sonlandırılmıştır. İksa duvarı üzerindeki köşe etkisi iki boyutlu programlar kullanılarak modellenemez. Bu nedenle iki boyutlu programda köşenin yatay destek (strut) olarak tanımlandığı bir model ile analiz yapılmıştır. Burada, incelenen kazıklara dik doğrultuda gelen komşu kenardaki kazıkların başlık ve kuşak kirişlerinin yatay destek olarak davrandığı düşünülmüştür. Başlık ve kuşak kirişlerinin rijitlik değeri ve kazıklar arası mesafe değeri aynı şekilde bu yatay destek elemanı için kullanılmıştır. Analiz sonuçlarında; strut elemanlı çözümde strut elemansız çözüme göre daha düşük deplasman değerleri elde edilmiş olup, bu deplasman değerlerinin aynı zamanda köşe noktasından alınan saha ölçümleri ile uyumlu olduğu görülmüştür. Bu sonuçlardan yola çıkarak köşe etkisinin ihmal edildiği durumlarda iki boyutlu sonlu eleman analiz programlarının saha ile uyumlu sonuçlar verdiği, ancak ihtiyaç duyulduğu durumlarda köşe etkisinin iki boyutlu analiz programlarına yansıtılabileceği görülmüştür.

The deflections, moments and effective earth pressures which occurs during excavation are mostly defined by using plain strain analysis methods. But the excavation behaviour is described as three dimensional. Most of excavations have corners and the corners can not be modeled by using two dimensional analysis programs.However the three dimensional analyses cause to increase the cost and lose a huge time at the beginning of the project desgining.The deflections acting on the wall during excavation were examined by many researchers and those studies show that the corner of an excavation pit affects the deflection behavior of the excavation wall. In this thesis, a deep excavation wall that is supported by anchors more than one level is analyzed using plane strain finite element program. An in-situ wall is also analyzed by modeling the corner as a strut to understand corner effect. Deflection, moment, effective lateral earth pressures and shear forces acting on the walls are examined to see the differences between the models with corner and without corner. Besides, safety factors of support systems have been calculated and compared to each other. A deep excavation case history namely Çiftçi Towers Zincirlikuyu is analyzed for this study. The deep excavation of the project is analyzed with two dimensional finite element analysis method by using program PLAXIS 2D V8.6. Two different wall models with corner and without corner are studied. The results of the analysis are compared with the field monitoring data and the effect of corner on wall behavior is examined. It is planned that two multiplex residence buildings with shopping center and parking areas will be constructed in the scope of Çiftçi Towers Zincirlikuyu Project. The project area is about 22.000 m².A foundation excavation which has a depth range that it changes between 36 m and 40 m was done in the scope of the project. The shoring system of the excavation applied at two benchs is composed of bored piles, mini pileswith supported by soil nails and prestressed anchors. In the scope of this study, the support system wall of Section-9 between the axis 10-11 has been analyzed. The support system of that section is composed of bored piles at the first bench and mini piles at the second bench.The wall is also supported by prestressed anchors. The corner is located at the second bench. General soil profile of the site is summarized as fill material for 0-18 m depth, multipart altered siltystone diabase or piece silty stone diabase from the below of the fill material to end of the borehole according to boring logs. No water table was observed at site. In the analysis, the soil profile of the examined section is defined as fill material for 0-3m depth and multipart altered siltystone diabase from 3m depth to end of the soil model according to the related boring log.  The deflection behavior of the Section-9 was monitored by using two inclinometers namely Inko-1 and Inko-2. The distances of those inclinometers to the corner are 2.5 m and 51 m, respectively. Eleven sets of readings were recorded from both of the inklinometers. Plaxis 8.6 finite element program has been used for the analysis of Section K-9. 15 nodded triangular elements have been used in the analyses. Plane strain models have been utilized by using medium level finite element mesh. The engineering parameters of the soil layers have been defined according to laboratory test results. Hardening Soil Model has been used for simulating the behaviors of the soil layers. As no water table was observed at site, drained material type has been selected in the analysis.For simulation of the road load, 150 kPa surcharge load has been applied. Excavation support system with two benchshave been analyzed and two different models have been created. 100 cm piles with 120 cm spacing and 24 m length at the first bench and 30 cm piles with 60 cm spacing and 20.1 m length at the second bench have been usedfor each model (Model-1 & 2). Pile walls are propped by eighteen levels anchors (4x0.6”) which were applied with 120 cm lateral spacing and lengths varying between 24.5 m and 39.5 m. 500 kN prestress load is applied for the anchors.  Corner effect can not be modeled by using two dimensional finite element analysis programs. It is thought that whether the top and cross beams of piles which are perpendicular to examined piles behave like strut. To check this, plain strain analysis with modeling the corner as a strut has been performed in the analysis of second model (Model-2). The calculated stiffness value of the beams and the lateral spacing value of the piles are assigned to that strut element. The anchor load for the model with corner is ignored to determine only the corner effect on the wall behavior. The strut elements are applied for the second bench excavation system piles because there is no corner point for the first bench excavation. Support system elements behaviours have been defined as lineer-elastic. The excavation modelshave been calculated by thirty eight phases and completed. At the beginning phase (Phase-0), Ko loading method has been performed to calculate effective stresses at the beginning status (at rest earth pressure) of the system because underground water level is quite deeper than system geometry. At Phase-1, 150 kPa sursharge load has been applied. At Phase-2, 100 cm diameter bored pile at the first bench has been activated. Between Phase-3 and Phase-19, excavation has been done and acnhors has been activated and prestressed in steps down to beginning level of second bench. At Phase-20, 30 cm diameter mini pile at the second bench has been activated. Between Phase-21 and Phase-37, excavation has been done and acnhors has been activated and prestressed in steps down to bottom level of excavation.In Model-2 (strutted system), only the strut elements have been activated to ignore anchor load effects on the corner. In the last phase (Phase-38), phi/c reduction analysis has been done to calculate the safety factor of the support system. Deflections, effective horizontal stresses, moments and shearing forces have been calculated for the excavation models by plain strain analyses. Comparisons between two models results have been done and presented as graphical to check the corner effect on the support system. Besides, the calculated deflection results of each excavation model have been compared to measurement results of two inclinometers which are placed at 2.5 m and 51 m distance from the corner. At the second bench where corner exists, maximum deflection valueshave been calculated as 27.9 mm for normal solution and 14 mm for strut solution. Calculated maximum effective horizontal stresses are 475.61 kN/m² for normal solution and 636.22 kN/m² for strut solution. Maksimum moments have been calculated as 99.97 kNm/m for normal solution and 168.43 kNm/m for strut solution. And maksimum shear force values are 346.77 kN/m for normal solution and 409.93 kN/m for strut solution. The deflections obtained from the Model-1 which has been analyzed without strut, are close to the measured values from the Inclinometer-2 which is at 51 m distance from the corner, but not similar to measured values from the Inclinometer-1. On the other hand, obtained deflections from Model-2 which has been analyzed by modeling the corner as a strut, match the measured values from Inclinometer-1 which is near to the corner.The difference between calculated deflections of Model-1 and Model-2 is nearly 14 mmand also the difference between measured deflections from Inko-1 and Inko-2 is nearly 20 mm at the second bench. Effective horizontal stresses obtained from each model have been examined and compared on graphs. It has been observed that the stresses of two models are similar down to second bench, but from the beginning of the second bench down to 32 m depth, it has been obtained that stresses of strut solution are higher than stresses of solution without strut. Additionally, moment and shear force values have been also examined and presented as graphically. It has been observed that the moment diagram of two models are similar down to second bench.From the beginning of the second bench down to 32 m depth, it is obtained that moment values of strut solution are higher than values of solution without strut, butfrom 32 m depth to the bottom of excavation they are decreasing compared to values of solution without strut. The similar changes have been observed also for shear forces diagram. Safety factors (FS) of the support systems have been calculated by phi/c reduction analysis at the last phase of calculations. For the solution without strut and with strut, safety factors have been obtained as 1.6644 and 2.1241, respectively. Critical slip circles have been examined and presented on plaxis results views. It has been observed that critical slip circles of model withstrutsolution are quite smaller than circles of model without strut. Calculated deflection values of strut solution are quite similar to measured values from inclinometer near to the corner. Deflection values calculated by normal analysis that ignores corner effect are also close to measurements of inclinometer placed at 51 m distance from the corner. It has been observed that the corner effect on deflections diminishes within a distance from the corner. Consequently, the analyses results show that two dimensional analysis method gives compatible results with site measurements and measured deflection values that are under corner effect can be observed by modeling corner as a strut with plain strain analyses method.
Two Dimensional Analysis Of Corner Effects In Deep Excavations
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2014
Thesis (M.Sc.) -- İstanbul Technical University, Instıtute of Science and Technology, 2014
Keywords: Köşe Etkisi; Derin Kazı; Derin Kazı Destek Sistemi; Düzlem Gerilme Analizi; İki Boyutlu Sonlu Eleman Analiz Yöntemi; Corner Effect; Deep Excavation; Deep Excavation Support System; Plain Strain Analysis; Two Dimensional Finite Element Analysis